2002
DOI: 10.1016/s0550-3213(02)00247-x
|View full text |Cite
|
Sign up to set email alerts
|

Multicharged dyonic integrable models

Abstract: We introduce and study new integrable models (IMs) of A (1) n -Non-Abelian Toda type which admit U(1) ⊗ U(1) charged topological solitons. They correspond to the symmetry breaking SU(n + 1) → SU(2) ⊗ SU(2) ⊗ U(1) n−2 and are conjectured to describe charged dyonic domain walls of N = 1 SU(n + 1) SUSY gauge theory in large n limit. It is shown that this family of relativistic IMs corresponds to the first negative grade q = −1 member of a dyonic hierarchy of generalized cKP type. The explicit relation between the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 49 publications
0
26
0
1
Order By: Relevance
“…Again, by integrating the auxiliary fields A + ,Ā − , one gets (1.1). More explicitly the ungauged multicharged A (1) n (p = 2) IM is given by [23] L u p=2 = 1 2…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Again, by integrating the auxiliary fields A + ,Ā − , one gets (1.1). More explicitly the ungauged multicharged A (1) n (p = 2) IM is given by [23] L u p=2 = 1 2…”
Section: )mentioning
confidence: 99%
“…We take eqn. (2.7) with g 0 ∈ G 0 = SL(2) ⊗ SL(2) ⊗ U(1) n−2 and A 0 = a 0 (z,z)(λ 1 + λ n ) · H,Ā 0 =ā 0 (z,z)(λ 1 + λ n ) · H, (a 0 ,ā 0 are arbitrary functions) and by performing the Gaussian integration over a 0 ,ā 0 we obtain the effective Lagrangian for the intermediate axial IM [23]…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that the sl(2) ATM model describes a confinement mechanism and the low-energy spectrum of QCD 2 (one flavor and N colors) [6]. Recently, some U (1) and U (1) x U (1) charged topological soliton solutions of certain class of affine Toda models have been interpreted as charged dyonic domain walls of 4D SU (N ) gauge theory and N = 1 SU (N ) SUSY gauge theory in the large N limit, respectively [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…10) and the fact that e T F e −T = F + [T, F ] + ..., we have[F − q , bF + q b −1 ] = i{ α(l−q,i) m ψ α(l−q,i) ψ α(l−q,i) Lψ α(l−q,i) R exp − n α(l−q,i) b K ba ϕ a l α(l−q,i) c + α(q,i) m ψ α(q,i)ψ α(q,i) L ψ α(q,i) R exp n α(q,i) b K ba ϕ a l α(q,i) c }H 0 c (7.11)…”
unclassified